A review of the classification and mechanism of action of battery-based sensors - Jiang, Taiyu (Transactions on Environment, Energy and Earth Sciences, 2026)
Safety monitoring and lifespan management of lithium-ion batteries are crucial for new energy applications. However, traditional battery management systems (BMS) rely solely on electrical signals such as voltage, current, and surface temperature, making it difficult to detect internal hazards in a timely manner. They also suffer from limitations such as delayed response and a single observable quantity. In recent years, new sensing technologies have been introduced into the interior and surface of batteries to acquire various physical information, such as heat and force, enabling in-situ monitoring of the battery status. This article systematically discusses the main categories of battery sensors and their mechanisms of action. It compares the latest research progress and performance indicators of technology routes such as fiber Bragg grating (FBG), non-dispersive infrared (NDIR), and MXene-based flexible sensors. It also summarizes engineering challenges and coping strategies, including packaging integration, signal decoupling, early warning algorithms, and multimodal fusion. The application value of sensing technology in battery SoC/SoH estimation, safety warnings, and fast charging adaptation is discussed. Finally, the future development directions of battery sensing technology, including non-intrusive sensing, wireless transmission integration, and the fusion of physical models and machine learning, provide guidance for the next generation of intelligent battery monitoring and management.
Keywords: Sensor classification; multi-physics coupling; FBG; BMS; SoC.